KOMUNIKASI PELAYANAN PUBLIK PEMERINTAH KABUPATEN SUMBA TIMUR MELALUI IMPLEMENTASI SITUS WEB BIDANG LAYANAN E-GOVERNMENT - Risca Bonita Siokain (Acta Diurna: Jurnal Ilmu Komunikasi, 2025)
This research utilizes the theories of public communication with the aim of understanding and analyzing how the public service communication of the East Sumba city government is carried out through the implementation of the e-Government service website, sumbatimurkab.go.id. This study is qualitative descriptive research employing a case study method. Overall, this study concludes that the Diskominfo government of East Sumba district has undertaken several efforts to realize public services for the community, including activities such as media gatherings, social media utilization, podcasts, booklets, creating an overview, and providing technical guidance to administrators and various departments of the East Sumba district. The e-Government service through the website sumbatimurkab.go.id is also acknowledged by Diskominfo, however, it is noted that the current state of the website sumbatimurkab.go.id is not yet sufficient, and digitalization services across various departments are lacking, posing a challenge to the lack of widespread digital based public services for the community. The government should prioritize the development of fundamental ICT infrastructure, such as stable internet networks, to assist marginalized communities in accessing online services. Consequently, various forms of innovation in public service communication implementation should be consistently pursued, accompanied by the readiness of supporting human resources.